Usefulness of cadaver embalming solutions as alternatives to formalin in veterinary surgical training - Moon, Je-Sung; Nam, Sung Min; Nahm, Sang-Soep; Yoon, Hun-Young (The Thai Journal of Veterinary Medicine, 2020)
Veterinary surgical training with live animals is inevitable for skill development. However, using a live animal is impractical owing to cost and ethical standards. Thus, well-embalmed life-like cadavers should be used. This study aimed to assess the usefulness of cadaver embalming in surgical training using two alternatives to formalin solution (FS)—Thiel’s solution (TS) and saturated salt solution (SS). Four groups, each comprising three Beagles, used FS, TS, and SS for cadaver embalming, and one group served as control. Skin elasticity, range of motion (ROM), tissue color, and life-like conditions during surgical procedures were evaluated at one-month intervals for a total of four months. Skin elasticity in the TS group was more similar to that of the control group in the first and second months, and to that in the SS group from the first to the third month, while that of the FS group was lower than that of the control group in the second and fourth months (P < 0.05). ROM in the TS group showed no difference than that in the control group (P > 0.05), while ROM in the FS group was lower than that in the control group (P < 0.05). Overall tissue color in the TS group was not different from that in the control group until the third month (P > 0.05). On evaluation of life-like conditions during surgical training, TS group cadavers tended to be superior to those in other groups in the first month (P < 0.05), but gradually decreased, and in the fourth month, the score was lower than those of the SS group (P < 0.05). TS cadavers showed the most life-like conditions with regard to elasticity, color, ROM, and surgical aspects and thus were suitable for surgical training within three months. This study is clinically relevant in minimizing animal sacrifice by effective and long-term conservation of quality cadavers.